The Influence of Radiographic Severity on the Relationship between Muscle Strength and Joint Loading in Obese Knee Osteoarthritis Patients. (28th March 2011) - Aaboe, Jens; Bliddal, Henning; Alkjaer, Tine; Boesen, Mikael; Henriksen, Marius
Abstract : Objective . To investigate the relationship between knee muscle strength and the external knee adduction moment during walking in obese knee osteoarthritis patients and whether disease severity influences this relationship. Methods . This cross-sectional study included 136 elderly obese (BMI > 30 ) adults with predominant medial knee osteoarthritis. Muscle strength, standing radiographic severity as measured by the Kellgren and Lawrence scale, and the peak external knee adduction moment were measured at self-selected walking speed. Results . According to radiographic severity, patients were classified as "less severe" (KL 1-2, N = 73 ) or "severe" (KL 3-4, N = 63 ). A significant positive association was demonstrated between the peak knee adduction moment and hamstring muscle strength in the whole cohort (P = .047 ). However, disease severity did not influence the relationship between muscle strength and dynamic medial knee joint loading. Severe patients had higher peak knee adduction moment and more varus malalignment (P < .001 ). Conclusion . Higher hamstring muscle strength relates to higher estimates of dynamic knee joint loading in the medial compartment. No such relationship existed for quadriceps muscle strength. Although cross sectional, the results suggest that hamstrings function should receive increased attention in future studies and treatments that aim at halting disease progression.